RecA Regulation by RecU and DprA During Bacillus subtilis Natural Plasmid Transformation - Serrano, Ester; Carrasco, Begoña; Gilmore, Jamie L.; Takeyasu, Kunio; Alonso, Juan C. (Frontiers in Microbiology, 2018)
Natural plasmid transformation plays an important role in the dissemination of antibiotic resistance genes in bacteria. During this process, Bacillus subtilis RecA physically interacts with RecU, RecX and DprA. These three proteins are required for plasmid transformation, but RecA is not. In vitro, DprA recruits RecA onto SsbA-coated single-stranded (ss) DNA, whereas RecX inhibits RecA filament formation, leading to net filament disassembly. We show that a null recA (recA) mutation suppresses the plasmid transformation defect of recU competent cells, and that RecU is essential for both chromosomal and plasmid transformation in the recX context. RecU inhibits RecA filament growth and facilitates RecA disassembly from preformed filaments. Increasing SsbA concentrations additively contributes to RecU-mediated inhibition of RecA filament extension. DprA is necessary and sufficient to counteract the negative effect of both RecU and SsbA on RecA filament growth onto ssDNA. DprA-SsbA activates RecA to catalyze DNA strand exchange in the presence of RecU, but this effect was not observed if RecU was added prior to RecA. We propose that DprA contributes to RecA filament growth onto any internalized SsbA-coated ssDNA. When the ssDNA is homologous to the recipient, DprA antagonizes the inhibitory effect of RecU on RecA filament growth and helps RecA to catalyze chromosomal transformation. On the contrary, RecU promotes RecA filament disassembly from a heterologous (plasmid) ssDNA, overcoming an unsuccessful homology search and favoring plasmid transformation. The DprA-DprA interaction may promote strand annealing upon binding to the complementary plasmid strands and facilitating thereby plasmid transformation rather than trough a mediation of RecA filament growth.